2010
DOI: 10.1577/m08-038.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Redd Superimposition by Introduced Kokanee on the Spawning Success of Native Bull Trout

Abstract: Intra‐ and interspecific competition for spawning space is a commonly observed interaction in salmonids that can result in progeny loss. This study examined the impacts of redd superimposition by kokanee Oncorhynchus nerka on the reproductive success of bull trout Salvelinus confluentus in the Deschutes River basin, Oregon. The activities of high‐density spawning groups of kokanee were hypothesized to place the eggs and alevins of bull trout at risk of displacement and damage wherever the spawning habitats of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…While not all studies have shown superimposition to have negative effects (Weeber and Giannico 2010), many studies indicate there are negative effects if the overlying redds are excavated as deep or deeper than the underlying redds (Hayes 1987;Sorensen et al 1995;Van Winkle et al 1998;Taniguchi et al 2000;Nomoto et al 2010), as we assume they would be with intraspecific superimposition. Under this assumption, any two superimposed redds in Lees Ferry would only functionally count as one, as the overlying redd would eliminate the viability of the underlying redd.…”
Section: Discussionmentioning
confidence: 92%
“…While not all studies have shown superimposition to have negative effects (Weeber and Giannico 2010), many studies indicate there are negative effects if the overlying redds are excavated as deep or deeper than the underlying redds (Hayes 1987;Sorensen et al 1995;Van Winkle et al 1998;Taniguchi et al 2000;Nomoto et al 2010), as we assume they would be with intraspecific superimposition. Under this assumption, any two superimposed redds in Lees Ferry would only functionally count as one, as the overlying redd would eliminate the viability of the underlying redd.…”
Section: Discussionmentioning
confidence: 92%
“…Current estimates of adult population size are extremely low; 10 redds/year, on average, were observed from 1996 to 2009. This low population size is caused in large part by interactions with nonnative fish, such as hybridization with brook trout, competition with lake trout S. namaycush, and potential bull trout redd superimposition by introduced kokanee Oncorhynchus nerka (Weeber et al 2010). Our estimates of within-population genetic diversity suggest that Odell Lake bull trout are at a high risk of extinction with an N e of 15 fish (95% CI = 10-24 fish) and low values for A R (2.75) and H E (0.38).…”
Section: Challenges For Bull Trout Conservationmentioning
confidence: 99%
“…Age and size at maturity are important traits in salmon that influence individual fitness, life history variation, population demographics, and fishery characteristics. Older age at maturity is associated with larger size in salmon which can improve reproductive success in females through increased fecundity (Healey and Heard 1984), greater egg size and maternal provisioning to offspring (Nicholas and Hankin 1988), and the ability to dig deeper redds which might be resistant to scouring and superimposition by other females (Berghe and Gross 1984, Weeber et al 2010). Male salmon exhibit alternative reproductive tactics associated with age at maturity in multiple salmon species (Maekawa and Onozato 1986, Gross 1991, Fleming 1996, Foote et al 1997).…”
Section: Introductionmentioning
confidence: 99%